2021
DOI: 10.5664/jcsm.9056
|View full text |Cite
|
Sign up to set email alerts
|

Are sleep paralysis and false awakenings different from REM sleep and from lucid REM sleep? A spectral EEG analysis

Abstract: Study objectives:To determine the polysomnography characteristics during sleep paralysis, false awakenings and lucid dreaming (which are states intermediate to REM sleep and wake but exceptionally observed in sleep laboratory). Methods:In 5 subjects, we captured 5 episodes of sleep paralysis (2 time-marked with the ocular left-right-left-right code normally used to signal lucid dreaming, 1 time-marked by an external noise and 2 retrospectively reported) and 2 episodes of false awakening. The sleep coding (usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 15 publications
5
44
0
Order By: Relevance
“…The specific case of false awakenings, which were very frequent in our study, is also consistent with the suggestion that LIDs are influenced by heightened REM sleep arousal. False awakenings were suggested to be a hyper-aroused REM sleep state [ 48 ], as recently evidenced by spectral EEG analysis [ 49 ]. Moreover, false awakenings frequently occur in association with lucid dreams [ 48 , 50 53 ] and sleep paralysis [ 50 , 53 ] both of which have also been proposed to be highly aroused, hybrid states with features of both REM sleep and waking [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specific case of false awakenings, which were very frequent in our study, is also consistent with the suggestion that LIDs are influenced by heightened REM sleep arousal. False awakenings were suggested to be a hyper-aroused REM sleep state [ 48 ], as recently evidenced by spectral EEG analysis [ 49 ]. Moreover, false awakenings frequently occur in association with lucid dreams [ 48 , 50 53 ] and sleep paralysis [ 50 , 53 ] both of which have also been proposed to be highly aroused, hybrid states with features of both REM sleep and waking [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such imbalance between sleep-like and wake-like patterns during sleep appears to be a common denominator of a wider variety of pathological sleep states ( SI Appendix , Table S1 ). In particular, relatively increased wake-like EEG activity was also observed in nightmare disorders ( 66 , 67 ), insomniac complaints ( 68 70 ), and sleep paralysis ( 71 , 72 ).…”
Section: Regulation Of Sleep and Arousal: Gating Luciditymentioning
confidence: 96%
“…Besides small population samples, studies featured methodological differences and a small number of scalp recording sites, and they often focused on specific (e.g., alpha) or narrow frequency ranges ( 4 ). The few sleep EEG studies consistently reported reduced sleep regulation signs and to some extent, increased wake-like activity in LD vs. non-LD, such as reduced power ( 71 , 81 , 82 ) and synchrony ( 82 ) in (1- to 4-Hz) low frequencies or increased alpha ( 83 ), parietal beta ( 84 ), or gamma ( 13 ) activity; however, the increase in fast frequencies (beta and gamma) was questioned more recently ( 82 , 85 ). Interestingly, lucid dreams were mainly observed ( 1 ) during phasic REM (i.e., REM periods with increased ocular activity).…”
Section: Regulation Of Sleep and Arousal: Gating Luciditymentioning
confidence: 99%
“…Moreover, even while sleeping we are not totally occluded from processing external stimuli and some sleep stages allow more perceptual processing than others. There is also research indicating a connection between the presence of altered states of consciousness during sleep, such as pre-lucid dreams (Tyson et al, 1984), sleep onset hallucinations (Takeuchi et al, 1994), sleep paralysis and false awakenings (Mainieri et al, 2020), and higher levels of alpha activity, which in turn has been linked to more external sensory perception (Tyson et al, 1984;Conduit et al, 1997;Darracq et al, 2018). Thus, we could speculate that during the state described by our participants, there was some integration of external stimuli which could have given place to some of the characteristic "Non-modal sensations" reported, such as those involving what could be considered as esoteric or mystical-like elements like "feeling the nothingness" or a "felt inner sound" (elements that could be taken to go above or beyond the realm of "reality" or what is possible in the natural world).…”
Section: Lack Of Sensory Perceptionmentioning
confidence: 99%